THE EFFECTS OF CARRYING THE M-SHAPE METHOD ON BONDING ATTACHMENT AND INFANT'S SLEEP QUALITY - Brivian Florentis Yustanta (Placentum, 2023)
Background: Carrying an infant using M-shape method is vital in creating a bond of affection (bonding attachment) between mother and infant. Carrying using the M-shape method makes the infant calmer and sleeps easier, because the face of infant facing the person carrying them